Moonraker [videorecording (DVD)] - Moore, Roger, 1927-2017; Chiles, Lois, 1947-; Lonsdale, Michaël, 1931-2020-; Fleming, Ian, 1908-1964
James Bond blasts into orbit in this pulse-pounding adventure that takes him from Venice, to Rio de Janeiro, and to outer space! Roger Moore stars for the fourth time as Agent 007 and joins forces with NASA scientist Holly Goodhead to prevent a power-mad industrialist from destroying all human life on Earth.